Effect of crumb rubber percentages and bitumen sources on high-temperature rheological properties of less smell crumb rubber modified bitumen. (29th March 2021) - Duan, Haihui; Zhu, Chongzheng; Li, Yanqi; Zhang, Henglong; Zhang, Shuai; Xiao, Feipeng; Amirkhanian, Serji
Highlights: Effects of a new CR with less smell on CRMB's performance are investigated. Variance analysis is adopted to compare effects of two factors on less smell CRMB. Besides less smell merit, new CR's addition can improve bitumen's performance. A low viscosity for CRMB with Inman leads to less energy consumption and emissions. Abstract: The smell generated by crumb rubber modified bitumen (CRMB) is unfavorable or offensive, leading to many complaints from people involved. Therefore, a new crumb rubber (CR) product with less smell has been developed. The study aims at investigating the influence of the new CR on high-temperature rheological properties of the CRMB derived from different bitumen sources. Besides, the effect degrees of the bitumen source and the new CR percentage on its rheological properties was compared with analysis of variance (ANOVA) method. The rheological properties tests were conducted on three base binders (Inman, Nustar and Kuwait) and the CRMB with less smell CR before and after rolling thin film oven test by Brookfield Viscometer and dynamic shear rheometer (DSR). The results show that similar to common CRs, the addition of the new CR can increase viscosity of the CRMB and improve high-temperature rheological properties of bitumen binders. CRMB exhibits a different viscoelastic behavior from the styrene-butadienestyrene block copolymer (SBS) modified bitumen, and the former has a wider linear region than the latter. But an increasing CR percentage leads to a narrower linear viscoelastic region for the CRMB. In case of the improvement of high-temperature rheological properties of bitumen binders, it is not only related to the CR percentages but bitumen source. Finally, ANOVA results indicate that bitumen source has a greater contribution than CR percentage to the high-temperature rheological properties of CRMB. On the basis of the results discussed, the CRMB produced from Nustar and with 15% new CR is recommended.